Perbandingan Struktur Anatomis, Sifat Fisis, dan Sifat Mekanis Kayu Jati Unggul dan Kayu Jati Konvensional Comparative Study on Anatomical Structure and Physical-Mechanical Properties between Tissue Cultural- and Conventional Teakwoods - Imam Wahyudi; Ahmad Faizal Arifien (Masyarakat Peneliti Kayu Indonesia, 2005)
Anatomical structure and some important properties of 3 years old tissues cultural Teakwood (Tectona grandis L.f.) were studied and compared to those of 3 and 8 years old conventional ones. Wood samples were obtained from standing trees of plantation forest area around Semarang city (Central Java). Anatomical structure was observed using wood section 20 µ thick, while fiber dimension was measured on individual macerated fibers. Physical and mechanical properties of wood were evaluated in accordance with BS 132:57 for small clear specimen using universal testing machine. All wood samples studied were still juvenile since wood density and fibers length tend to increase from pith towards the bark. Both 3 years-old woods, namely tissue cultural and the conventional Teakwoods have not heartwood at the center or the end of the stem except on their basal i.e. 29.81% in the former and 25% in the latter, respectively. The 8 years old conventional Teakwood consisted of 58.23% heartwood at the basal, and 46.30% at the center, respectively. Latewood portion of tissue cultural teakwood was the lowest. Difference between earlywood and latewood in this Teak was unclear and not distinguished well. Wood texture among the samples was moderate. The finest was found on tissue cultural Teakwood while the roughest on the conventional 3 years old. Based on their average in wood density, specific gravity, modulus of elasticity and modulus of rupture, it can be said that quality of tissue cultural Teakwood was similar to that of 3 years-old conventional one, but much lower than that of 8 years-old conventional Teakwood although their stem diameters were similar physically. This coincides well with their anatomical characteristics.